Deliberative Public Engagement with Science An Empirical Investigation - PytlikZillig, Lisa M. (SpringerBriefs in Psychology,, 2018)
This compact open access reference delves beyond popular concepts of educated consumers and an informed public by examining the science behind deliberative engagement. Using data from four longitudinal studies, the authors assess public engagement methods in deliberative discussions of ethical, legal, and social issues concerning innovations in nanotechnology. Coverage includes the theoretical origins of the studies, forms of engagement and variations used, and in-depth details on cognitive, affective, and social components that go into the critical thinking process and forming of opinions. Not only are the findings intriguing in and of themselves, but researchers from varied fields will also find them useful in pursuing their own projects. Featured in the coverage: Experimental methods and measures used in relation to specific outcomes. Forms of deliberative engagement affecting objective and subjective knowledge. Effects of engagement variables on attitude formation, change, and polarization. Tracing the processes leading to policy acceptance and support. Study conclusions and evaluation. Plus supplemental materials giving readers access to full study data. Since public engagement methods are widely regarded as valuable for policy input, planning purposes, and understanding societal processes, Deliberative Engagement with Science stands to have a wide audience among psychologists, researchers, academics, and policymakers, as well as professionals in the corporate sphere and the tech industries.